Reorienting Criminal Law Enforcement Based on Restorative Justice: Aligning The Principles of Victim Restitution, Legal Certainty, and The Revision of The National Criminal Code - Yulius Harya Pamungkas (Journal of Social Research, 2026)
Criminal law enforcement traditionally emphasizes punitive measures, often neglecting the needs of victims and the broader social community. In Indonesia, this approach has led to insufficient attention to victim restitution, perpetrator accountability, and social harmony. This study aims to analyze the position of restorative justice within Indonesian criminal law, assess the alignment of the National Criminal Code with restorative principles, and propose a synchronization model to ensure effective and equitable implementation. A normative legal research design was employed, utilizing primary legal materials, including Law Number 1 of 2023, Peraturan Jaksa (Prosecutor's Regulation) Number 15 of 2020, and Peraturan Kepolisian (Police Regulation) Number 8 of 2021. Secondary materials consisted of scholarly articles, books, and international guidelines on restorative justice. Data were analyzed using qualitative content analysis to interpret legal norms, compare institutional arrangements, and identify gaps in procedural standards. The findings reveal that while Indonesian regulations have incorporated restorative principles, implementation remains fragmented, with varying standards across police, prosecutors, and courts. Restorative justice can enhance victim protection, encourage perpetrator accountability, and restore social balance, but requires clear normative boundaries, procedural safeguards, and institutional oversight. The study concludes that a synchronized model integrating case selection, victim protection, perpetrator accountability, and alignment with the Kitab Undang-Undang Hukum Pidana (National Criminal Code) can facilitate consistent, legally sound, and socially responsive criminal justice practices in Indonesia.